Pengaruh Adversity Quotient dan Emotional Quotient Terhadap Prestasi Belajar Matematika Siswa Kelas VIII MTs Negeri 3 Mataram Tahun Ajaran 2024/2025 - Aulia, Baiq Risma; Subarinah, Sri; Supiarmo, M. Gunawan (FKIP Universitas Mataram, 2025)
Low student math learning achievement is still a problem that is often encountered. Internal factors such as adversity quotient and emotional quotient are thought to influence student learning achievement. This study aims to determine the effect of adversity quotient and emotional quotient on students' mathematics learning achievement both partially and simultaneously. This research uses a quantitative approach with ex post facto method. The population of this study was class VIII as many as 200 students. The sample used was 133 students who were determined using purposive sampling technique. The instruments in this study were adversity quotient questionnaire, emotional quotient questionnaire and math learning achievement test. The instruments were validated by two experts. By using regression analysis, the results obtained: 1) there is a positive and significant effect of adversity quotient on mathematics learning achievement of students in class VIII MTsN 3 Mataram in the 2024/2025 school year with a contribution of 7.2%; 2) there is a positive and significant effect of emotional quotient on mathematics learning achievement of students in class VIII MTsN 3 Mataram in the 2024/2025 school year with a contribution of 12.9%; 3) there is a positive and significant effect of adversity quotient and emotional quotient on mathematics learning achievement of students in class VIII MTsN 3 Mataram in the 2024/2025 school year with a contribution of 11.7%.